Surat Al-Asr: The Philosophy of building the individual & society - Sulaiman Bin Ali Bin Amer Al Shuaili (Sultan Qaboos University, 2009)
The human being is a complicated creature in the universe. Allah has given him tremendous abilities to play his role as "khalifa" on the earth. In order to be able to play this role, Allah provided him with a special educational approach which is explained in the Quran. Surat Alasr is a manifestation of this approach which contains important elements for building people society. This study gives a brief introduction about the human being & the importance of time in our life. It also emphasizes "belief & act" as essential elements for building people. The study also shows the importance of advising people to take care of themselves & their societies. Some recommendations are suggested.